Morphology of Ganymede's FUV auroral ovals. Issue 3 (3rd March 2017) - Musacchio, Fabrizio; Saur, Joachim; Roth, Lorenz; Retherford, Kurt D.; McGrath, Melissa A.; Feldman, Paul D.; Strobel, Darrell F.
Abstract: We study the morphology of Ganymede's FUV aurora by analyzing spectral images obtained over the past two decades by the Space Telescope Imaging Spectrograph on board the Hubble Space Telescope. The observations cover the eastern and western elongation as well as various magnetic latitudes of Ganymede within the Jovian plasma sheet. We find both asymmetries in the spatial distribution of auroral brightness on the observed moon disk and temporal variation correlated to Ganymede's changing magnetic latitude. The total disk brightness is on average 1.42 ± 0.07 times brighter on the leading side (95.4 ± 2.1 R) than on the trailing side (67.2 ± 2.9 R). The brightness ratio of the sub‐Jovian hemisphere to the anti‐Jovian hemisphere is 1.81 ± 0.06 on the leading side and 1.41 ± 0.14 on the trailing side, respectively. Inside the Jovian current sheet, the brightness of the auroral ovals increases by a factor of 1.45 ± 0.02 on the leading side and decreases by a factor of 0.80 ± 0.02 on the trailing side. At the current sheet center, the auroral ovals shift 4.1° ± 0.7°latitude toward Ganymede's planetographic equator on the leading side and 2.9° ± 1.5° toward the poles on the trailing side. Both effects, the variation of brightness and the movement of the ovals are correlated to a stronger interaction of Jupiter's magnetospheric plasma with Ganymede's minimagnetosphere inside the current sheet. Finally, we calculate the latitudinal difference of the northern and southern ovals from Ganymede's magnetic equator. The result suggests a farther westward orientation of Ganymede's dipole magnetic moment at approximately 47° + 58°/−43°west longitude compared to previous estimates. Key Points: Brightness and locations of Ganymede's auroral ovals change periodically with position in Jupiter's magnetosphere Aurora is brighter on the Jovian facing side and on the leading side of Ganymede Auroral observations can help to constrain Ganymede's dynamo magnetic field